The Application of Maslow's Theory to The Work Motivation of Village Heads - Siti Adira Kania; Leni Rohida (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2026)
The problem in this study is to determine how the application of Abraham Maslow's theory can explain the work motivation of village officials, especially hamlet heads, in Maniskidul Village, due to the imbalance in the fulfillment of work needs at each hierarchy of needs according to the theory. The objective of this study is to identify the elements that determine the work motivation of hamlet heads. This study adopts an interpretive qualitative methodology, including participatory observation, in-depth discussions, and a review of archives relevant to the research. The results indicate that financial compensation, health insurance, and employment security relatively fulfill physiological and safety needs. Harmonious village-community relations and mutual cooperation enable the fulfillment of social needs. However, there are no adequate competency development and reward mechanisms to fulfill the needs for self-actualization, esteem, and beauty. This condition shows that social affiliation and cultural legitimacy have a greater influence on the motivation of hamlet heads than formal incentives. According to the study, village bureaucratic reform must accommodate the fulfillment of higher-level needs by implementing a reward system, work environment management, and training. For more comprehensive and measurable results, it is recommended that the study be expanded using a mixed method.